2009
DOI: 10.1002/jnr.22225
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of peroxisome proliferator‐activated receptors γ coactivator‐1α against neuronal cell death in the hippocampal CA1 subfield after transient global ischemia

Abstract: Peroxisome proliferator-activated receptors gamma coactivator-1alpha (PGC-1alpha) may regulate the mitochondrial antioxidant defense system under many neuropathological settings. However, the exact role of PGC-1alpha in ischemic brain damage is still under debate. Based on an experimental model of transient global ischemia (TGI), this study evaluated the hypothesis that the activation of PGC-1alpha signaling pathway protects hippocampal CA1 neurons against delayed neuronal death after TGI. In Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 37 publications
3
76
0
Order By: Relevance
“…This faster metabolism results in more respiratory chain electron leakage (1-2 % of transported electrons leak to generate ROS) [131] and is counter-balanced by enhanced synthesis of proteins involved in ROS scavenging. PGC-1α increases expression of thioredoxin, manganese superoxide dismutase (MnSOD), peroxiredoxin, and UCP2 in neurons, endothelial cells, and myocardium [89,132,133]. Interestingly, MnSOD expression is down in DRG in diabetes and correlates with higher ROS levels in axons [27,53].…”
Section: Links Between Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…This faster metabolism results in more respiratory chain electron leakage (1-2 % of transported electrons leak to generate ROS) [131] and is counter-balanced by enhanced synthesis of proteins involved in ROS scavenging. PGC-1α increases expression of thioredoxin, manganese superoxide dismutase (MnSOD), peroxiredoxin, and UCP2 in neurons, endothelial cells, and myocardium [89,132,133]. Interestingly, MnSOD expression is down in DRG in diabetes and correlates with higher ROS levels in axons [27,53].…”
Section: Links Between Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…29 PGC1a is induced by cerebral ischemia and provides a neuroprotective effect against ischemic brain injury in the hippocampus by ameliorating oxidative stress. 30 An increased PGC-1a expression protects cultured neural cells from oxidative stress-mediated cell death. 27 Icariin protects against brain ischemic injury by increasing SIRT1 and PGC1a expression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PGC-1α regulates oxidative phosphorylation, mitochondrial biogenesis and respiration (22,23). Numerous previous studies have suggested that ischemia and hypoxia significantly induce the expression of PGC-1α (5)(6)(7)(8)(9)(10)(11)24,25). Arany et al (12) reported that PGC-1α was able to upregulate the expression of angiogenic factors such as VEGF, and promote the formation of new blood vessels in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Under ischemic and hypoxic conditions, the expression and transcriptional regulation activity of PGC-1α is enhanced in rat cardiac myocytes (5,6) and brain cells (7,8), rabbit renal tubular cells (9), and human skeletal muscle cells (10,11). A previous study demonstrated that PGC-1α is able to regulate an angiogenic program including vascular endothelial growth factor (VEGF) and additional angiogenic factors, in cultured muscle cells and skeletal muscle in vivo (12).…”
Section: Introductionmentioning
confidence: 99%